MODERN SCIENTIFIC AND RESEARCH WORK OF THE TEACHING STAFF DURING 2020-2024 AND PROSPECTS FOR ITS DEVELOPMENT FOR THE PERIOD UNTIL 2030 AT LVIV MEDICAL UNIVERSITY - Fedorov, Юрій; Kovpak, Альона (Actual Problems of Medicine and Pharmacy, 2025)
The article highlights the challenges faced by the healthcare sector and the teaching staff of the Lviv Medical University in the period 2020–2024. The consequences of the COVID-19 pandemic are described, in particular its impact on patients with comorbidities, as well as psychoneurological manifestations among the population. The current post-COVID challenges, the increase in the incidence of acute respiratory viral infections, influenza, injuries and mental disorders among military and civilian personnel, determined by the ICD-11, are considered. Attention is focused on the need for an interdisciplinary approach to medical practice, the introduction of new medicines, and the improvement of medical and legal relations in the “doctor-patient-pharmacist” system. The scientific potential of the university is presented, which is realized through the activities of four scientific schools, holding annual scientific and practical conferences with international participation, and publications in a professional electronic journal. The importance of institutional support for reforming the medical system in accordance with the Healthcare Development Strategy until 2030 is emphasized.